Precipitation alters the CO 2 effect on water‐use efficiency of temperate forests - Soumaya Belmecheri; R. Stockton Maxwell; Alan H. Taylor; Kenneth J. Davis; Rossella Guerrieri; David J. P. Moore; Shelly A. Rayback (Global Change Biology, 2021)
Increasing water‐use efficiency (WUE), the ratio of carbon gain to water loss, is a key mechanism that enhances carbon uptake by terrestrial vegetation under rising atmospheric CO 2 ( c a ). Existing theory and empirical evidence suggest a proportional WUE increase in response to rising c a as plants maintain a relatively constant ratio between the leaf intercellular ( c i ) and ambient ( c a ) partial CO 2 pressure ( c i / c a ). This has been hypothesized as the main driver of the strengthening of the terrestrial carbon sink over the recent decades. However, proportionality may not characterize CO 2 effects on WUE on longer time‐scales and the role of climate in modulating these effects is uncertain. Here, we evaluate long‐term WUE responses to c a and climate from 1901 to 2012 CE by reconstructing intrinsic WUE (iWUE, the ratio of photosynthesis to stomatal conductance) using carbon isotopes in tree rings across temperate forests in the northeastern USA. We show that iWUE increased steadily from 1901 to 1975 CE but remained constant thereafter despite continuously rising c a . This finding is consistent with a passive physiological response to c a and coincides with a shift to significantly wetter conditions across the region. Tree physiology was driven by summer moisture at multi‐decadal time‐scales and did not maintain a constant c i / c a in response to rising c a indicating that a point was reached where rising CO 2 had a diminishing effect on tree iWUE. Our results challenge the mechanism, magnitude, and persistence of CO 2 's effect on iWUE with significant implications for projections of terrestrial productivity under a changing climate.